Edukasi Jaringan dan Kemitraan: Melalui Komunitas Paduan Suara di Sekolah Citra Berkat dan Sekolah Ciputra Kasih Surabaya - SITEPU, RISMAWATI BR; Pranoto , Henry S; Dewi, Liliana; Soeparto, Wahyudi Henky; Soetedja, Venny (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PKM) activity was carried out by a team from Ciputra University Surabaya at Citra Berkat School (SCB) and Citra Kasih School (SCK) Surabaya with a primary focus on strengthening networks, collaborative education, and human resource development through the student choir community. This program aims to increase the capacity of participants, especially in the aspects of motivation, self-development, and the ability to work together as an arts community. The approach used included motivational training, learning the concept of Ikigai to help students find personal purpose and meaning in musical activities, and mentoring collaborative practices to create a positive and productive learning environment. The results of the activity showed that students gained a better understanding of their potential, the role of the community in character development, and the importance of networks and partnerships in supporting the creative process and improving the quality of choirs. This program is expected to become a model for sustainable collaboration between universities and schools in supporting the achievement of the SDGs, especially point 4 (Quality Education) and point 17 (Partnerships for the Goals).